SHOULD APPRECIATION BE BROUGHT INTO THE ACCOUNTS? - Fryxell, Carl A. (The Accounting Review, 1930)
Abstract The existence of appreciation, as evidenced by a fairly permanent increase in values, must in many cases be conceded. Such increase may be indicated by actual appraisal or by other data or information; and may be formally recognized by action of a Board of Directors. Various arguments have been advanced both for and against bringing appreciation into the accounts. Of the three or four leading arguments for the bringing of appreciation into the accounts, one which is usually advanced is that insurance of properties requires that the books show such properties at present values. It is a fact that the very purpose of insurance means the use of replacement costs in order that any destroyed property may be fully duplicated. A second argument is that refinancing whether by bond issue or short-term commercial paper, is facilitated if the balance sheet shows the mortgaged property at full present value. A third occasion for recognizing appreciation is in the case of sale, of the merger of several concerns. In this event a new value is usually placed upon the properties of the companies to be sold or merged.